Comparative bioinformatic analysis by RNA-seq of patients from Regional Hospital of Malaga with two types of lung cancer - Hashim, Ahmed (My University, 2021)
Differentially genes expressed were identified using iDEP tool. A total of 4513 DEGs were identified in LUAD and 5369 in LUSC. The upregulated and downregulated genes were applied to analyze the GO: biological process, cellular component, molecular function, and KEGG pathway of each type. The highly significant genes in both LUSC and LUAD were enriched in terms that linked with cell cycle and division, chromosome and chromosomal regions, and DNA repair and building. In LUSC the KEGG pathways enriched by the upregulated genes were basal cell carcinoma, mismatch repair, biosynthesis of cofactors, and pentose and glucuronate interconversions, while in LUAD, the KEGG pathways which focused on signaling pathways were enriched by downregulated genes and metabolic pathways which were enriched by upregulated genes. A protein-protein interaction network was constructed based on the STRING database, and the network was visualized and analyzed by Cytoscape app. From the protein-protein interaction network, hub genes were identified. A total of 9 genes in LUSC and 11 genes in LUAD were determined as candidate hub genes, 6 hub genes EGFR, CDK1, IL6, GAPDH, CCNB1, and CDH1 were common in both LUSC and LUAD. Validation of expression of candidate hub genes was applied based on the TCGA database using GEPIA tool, and the validation was identical to our results. The analysis of gene alteration, overall survival, and clinical parameters of hub genes was performed based on TCGA database using cBioPortal. In clinical parameters, the correlation between gene expression of hub genes and disease stages was examined, as no clear correlation was observed between variance in gene expression and the first three stages of the disease. The results obtained in this study may help in understanding more about the molecular mechanisms and the functional pathways that intersect and differ between LUSC and LUAD, and this may enhance the opportunities for new strategies for prevention and treatment.
Lung cancer is caused by several factors, passes through several stages, and has a variety of histological subtypes. The two most common subtypes of lung cancer are lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC), which are fall under the non-small-cell lung cancers (NSCLC) type. There are several similarities and differences between these two types in terms of anatomy, pathogenesis, risk factors, clinical presentation, diagnosis, and other factors. Therefore, it is necessary to investigate these factors by analyzing the gene expression in each type and comparing the results between the two types. The present study aimed to perform a comparative analysis of differential gene expression of RNA_seq data between LUSC and LUAD, and depending on the determination of differentially expressed genes in each type, we can perform analysis on Gene Ontology and KEGG pathways, as well as construct a protein-protein interaction network through which we can identify key genes for each of LUAS and LUAD.
Keywords: Bioinformática; Pulmones - Cáncer; Ciencias - Trabajos fin de máster; Bioinformatics; Lung cancer; RNA-seq; Differential expression